Model Sinektik Berbantuan Lembar Main Huruf untuk Meningkatkan Sikap Kritis dan Menulis Permulaan Siswa Kelas I - Adindari, Sabrina Ayu; Purwati, Panca Dewi (Lembaga Yasin AlSys, 2025)
Although early writing instruction has been widely recognized as a crucial component of primary education, studies that specifically examine the integration of the Synectics model with Lembar Kerja Peserta Didik (LKPD) Main Huruf to enhance beginning writing skills and students’ critical reasoning remain limited. This study aimed to evaluate the effectiveness of implementing the Synectics model combined with the Main Huruf worksheet in improving first-grade students’ beginning writing skills and critical thinking dispositions. A mixed-methods approach with a convergent parallel design was employed, involving 18 first-grade students at SD Negeri Gisikdrono 02 selected through total sampling. Data were collected through classroom observations and pretest–posttest assessments and were analyzed using descriptive statistics and qualitative thematic analysis. The findings showed a significant improvement in beginning writing skills, indicated by an increase in the mean score from 66.5 to 79 and an N-Gain value of 0.37 (medium category). Indicators of critical thinking, including analysis, explanation, and drawing conclusions, also improved, with 67–72% of students demonstrating stronger reasoning abilities. These results contribute to the reinforcement of constructivist learning theory by demonstrating that analogy-based and manipulative activities can deepen students’ cognitive engagement. The study concludes that the Synectics model assisted by the LKPD Main Huruf is effective in developing early-grade students’ linguistic and cognitive abilities and recommends that teachers integrate analogy-based and interactive activities into literacy instruction. Further research is advised to develop digital media and employ longitudinal designs to examine the sustainability of literacy development.